Damage-control resuscitation and emergency laparotomy: Findings from the PROPPR study. Issue 4 (April 2016) - Undurraga Perl, Vicente J.; Leroux, Brian; Cook, Mackenzie R.; Watson, Justin; Fair, Kelly; Martin, David T.; Kerby, Jeffrey D.; Williams, Carolyn; Inaba, Kenji; Wade, Charles E.; Cotton, Bryan A.; Del Junco, Deborah J.; et al.
Abstract : BACKGROUND: The Pragmatic Randomized Optimal Platelet and Plasma Ratios (PROPPR) trial has demonstrated that damage-control resuscitation, a massive transfusion strategy targeting a balanced delivery of plasma–platelet–red blood cell in a ratio of 1:1:1, results in improved survival at 3 hours and a reduction in deaths caused by exsanguination in the first 24 hours compared with a 1:1:2 ratio. In light of these findings, we hypothesized that patients receiving 1:1:1 ratio would have improved survival after emergency laparotomy. METHODS: Severely injured patients predicted to receive a massive transfusion admitted to 12 Level I North American trauma centers were randomized to 1:1:1 versus 1:1:2 as described in the PROPPR trial. From these patients, the subset that underwent an emergency laparotomy, defined previously in the literature as laparotomy within 90 minutes of arrival, were identified. We compared rates and timing of emergency laparotomy as well as postsurgical survival at 24 hours and 30 days. RESULTS: Of the 680 enrolled patients, 613 underwent a surgical procedure, 397 underwent a laparotomy, and 346 underwent an emergency laparotomy. The percentages of patients undergoing emergency laparotomy were 51.5% (174 of 338) and 50.3% (172 of 342) for 1:1:1 and 1:1:2, respectively ( p = 0.20). Median time to laparotomy was 28 minutes in both treatment groups. Among patients undergoing an emergency laparotomy, the proportions of patients surviving to 24 hours and 30 days were similar between treatment arms; 24-hour survival was 86.8% (151 of 174) for 1:1:1 and 83.1% (143 of 172) for 1:1:2 ( p = 0.29), and 30-day survival was 79.3% (138 of 174) for 1:1:1 and 75.0% (129 of 172) for 1:1:2 ( p = 0.30). CONCLUSION: We found no evidence that resuscitation strategy affects whether a patient requires an emergency laparotomy, time to laparotomy, or subsequent survival. LEVEL OF EVIDENCE: Therapeutic study, level IV.